2019
DOI: 10.1101/533059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Orexin-1 Receptor Signaling in Demand for the Opioid Fentanyl

Abstract: The orexin system is a potential treatment target for drug addiction. Orexin-1 receptor (OxR1) antagonism reduces demand for cocaine and remifentanil indicating that orexin-based therapies may reduce demand for many classes of abused drugs. However, pharmacokinetics vary greatly among opioids and it is unclear if OxR1 antagonism would reduce demand for all opioids, particularly ones with particularly high abuse liability. Here, we establish a behavioral economics (BE) procedure to assess the effects of OxR1 an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…4B ; ␤ ϭ 0.438, p ϭ 0.118). Baseline demand has also been shown to predict the antimotivational effects of systemic SB treatment (James et al, 2019;Fragale et al, 2019). Consistent with such previous findings, baseline ␣ was negatively correlated with intra-VP SB efficacy (1.0 mM; Fig.…”
Section: Baseline Demand For Remifentanil Predicts Cue-induced Reinstsupporting
confidence: 88%
See 4 more Smart Citations
“…4B ; ␤ ϭ 0.438, p ϭ 0.118). Baseline demand has also been shown to predict the antimotivational effects of systemic SB treatment (James et al, 2019;Fragale et al, 2019). Consistent with such previous findings, baseline ␣ was negatively correlated with intra-VP SB efficacy (1.0 mM; Fig.…”
Section: Baseline Demand For Remifentanil Predicts Cue-induced Reinstsupporting
confidence: 88%
“…We also reported that systemic blockade of OxR1s attenuated cue-induced reinstatement of heroin, fentanyl, and remifentanil seeking (Smith and Aston-Jones, 2012;Porter-Stransky et al, 2017;Fragale et al, 2019). Using within-session behavioral economics (BE) procedures, we recently found that systemic OxR1 antagonism decreased demand for fentanyl and remifentanil (Porter-Stransky et al, 2017;Fragale et al, 2019). Together, these results support a role for OxR1 signaling in opioid addiction.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations